2021 changes to the energy efficiency requirements of the Building Regulations for domestic buildings : Affecting new domestic buildings and existing domestic buildings when relevant building work is carried out : Final Stage Impact Assessment.: Affecting new domestic buildings and existing domestic buildings when relevant building work is carried out : Final Stage Impact Assessment. (2021) - Unknown
No abstract available